Development of Population Data Collection Applications in Vital Village Based on Mobile Web - Mardiyanto Mardiyanto; Febri Herniyanti; Noca Yolanda Sari (JTKSI (Jurnal Teknologi Komputer dan Sistem Informasi), 2021)
The implementation of rural community services is currently still facing problems with an ineffective government system and the lack of human resources in rural institutions. Population administration is one of the most important points in administrative governance in the village. One of them is population data collection at the Kejayaan Village office which has limited access to the population service process manually, so errors often occur and are less accurate in managing population data. In this research, a mobile web-based population data collection application will be designed using the SDLC (System Development Life Cycle) method. Which starts from System Design, System Design, Web Development / Coding, Testing, Implementation, and Maintenance. The flow in this study is described in the form of a Flowchart. The results of the study. a mobile web-based population data collection application that can be accessed via a smartphone can provide convenience for the village government in processing population data and can also provide information on the potential development of the Kejayaan Village. In addition, the village community can update their population data directly and make it easier for the community to obtain the latest information about the village and the village profile.